Study of Osmotic Behavior of Astasia longa and Dunaliella salina Cells as an Important Stage in Developing Their Cryopreservation Protocol - Chernobai, Nadiia; Vozovyk, Krystyna; Kadnikova, Nataliya; Rozanov, Leonid (. Biol. Life Sci. Forum 2022, 11, 59., 2021)
The study of osmotic parameters of cells is an important step in successful cryopreservation. The aim of this work is to study the osmotic reactions of cells of different taxonomic groups (euglenoid Astasia longa, microalga Dunaliella salina) in response to complementing with promising cryoprotectants (Me2SO, glycerol, ethanol) under normothermic conditions. Studies have shown that D. salina cells are osmotically tolerant to different concentrations of promising cryoprotectant solutions, whereas A. longa is more vulnerable to osmotic stress and can withstand only short-term exposure with 1–5% solutions of ethanol and glycerol.
Chernobai, N.; Kadnikova, N.; Vozovyk, K.; Rozanov, L. Study of Osmotic Behavior of Astasia longa and Dunaliella salina Cells as an Important Stage in Developing Their Cryopreservation Protocol. Biol. Life Sci. Forum 2022, 11, 59. https:// doi.org/10.3390/IECPS2021-11939
Keywords: microalgae; Astasia longa; Dunaliella salina; osmotic reactions; cryopreservation; cryoprotectant solutions